Emerging Roles for CSF-1 Receptor and its Ligands in the Nervous System. Issue 6 (June 2016) - Chitu, Violeta; Gokhan, Şölen; Nandi, Sayan; Mehler, Mark F.; Stanley, E. Richard
Abstract : The colony-stimulating factor-1 receptor (CSF-1R) kinase regulates tissue macrophage homeostasis, osteoclastogenesis, and Paneth cell development. However, recent studies in mice have revealed that CSF-1R signaling directly controls the development and maintenance of microglia, and cell autonomously regulates neuronal differentiation and survival. While the CSF-1R-cognate ligands, CSF-1 and interleukin-34 (IL-34) compete for binding to the CSF-1R, they are expressed in a largely non-overlapping manner by mature neurons. The recent identification of a dominantly inherited, adult-onset, progressive dementia associated with inactivating mutations in the CSF-1R highlights the importance of CSF-1R signaling in the brain. We review the roles of the CSF-1R and its ligands in microglial and neural development and function, and their relevance to our understanding of neurodegenerative disease. Trends: CSF-1R is a receptor tyrosine kinase with two cognate ligands, CSF-1 and IL-34, that are expressed in largely non-overlapping areas of the CNS and that regulate microglial proliferation, and survival. The CSF-1R is also expressed in neural progenitor cells and regulates their survival, proliferation and neuronal differentiation. Upregulation of CSF-1R expression in injured neurons promotes survival. Mutations in the CSF1R gene lead to an autosomal dominant, neurodegenerative disorder known as adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP). The Csf1r +/− mouse is a validated model for testing therapeutic strategies for ALSP. CSF-1R ligands and inhibitors are potential modulators of several neurological diseases including Alzheimer's disease, globoid cell leukodystrophy (Krabbe's disease), Charcot–Marie–Tooth disease, multiple sclerosis, and glioma.